Bioinspired MoS2 Nanosheet‐Modified Carbon Fibers for Synergetic Bacterial Elimination and Wound Disinfection. Issue 8 (21st December 2022) - Tang, Yanan; Qin, Zhen; Zhong, Yinghui; Yan, Xianqiang; Kong, Liang; Yang, Xiangyu; Yin, Shengyan; Li, Mo; Liu, Zhenning; Sun, Hang
Abstract: Bacterial infection is one of the most frequent wound complications and has become a major public health concern. Increasing resistance to antibiotics has been noted with these agents broadly used in wound management. It is an urgent demand to develop alternative antibacterial strategies with a reduced chance of resistance. Herein, a Nepenthes ‐mimicking nanosheet array of MoS2 on carbon fibers (CF‐MoS2 ) is proposed to achieve dual bactericidal activities. First, the sharp edges of synthesized surfaces are capable of inducing physical disruption of cell membranes, demonstrating mechanical antibacterial activity like their natural counterparts. Second, in the presence of near‐infrared light, bioinspired CF‐MoS2 nanosheets are able to cause the death of damaged bacteria owing to their inherent photothermal properties. Such dual‐functional modes endow the surfaces with nearly 100% killing efficiency for highly concentrated Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ). Furthermore, their potential to be applied as wound dressings for photothermal treatment of infectious wounds is also investigated in vivo. Bioinspired CF‐MoS2 dressings show advantages of synergistic disinfection and efficient promotion of wound regeneration. It is foreseen that this high‐performance and multifunctional CF‐MoS2 could afford a feasible broad‐spectrum treatment for non‐antibiotic disinfection. Abstract : Herein, Nepenthes ‐mimicking nanosheet arrays of MoS2 on carbon fibers (CF‐MoS2 ) are proposed to achieve reinforced antibacterial effect through mechanical rupture and photothermal behavior. Such dual‐functional modes endow the surfaces with nearly 100% killing efficiency for highly concentrated E. coli and S. aureus . Furthermore, bioinspired CF‐MoS2 dressings show the advantages of synergistic disinfection and the efficient promotion of wound regeneration.